A new flow pattern map for flow boiling of R410A in horizontal micro-fin tubes considering the effect of the helix angle. (January 2020) - Yang, Cheng-Min; Hrnjak, Pega
Abstract: This paper presents an improved flow pattern map for flow boiling in horizontal micro-fin tubes considering the effect of helix angle. The proposed map is modified from the one developed for horizontal smooth tubes by Wojtan et al. (2005) and takes the early transition to annular flow due to micro-fin geometry into account. Visualization of R410A flow boiling is carried out through the transparent smooth and micro-fin tubes with 0°, 10° and 18° helix angle and plotted on the proposed map for comparison. The result shows that the flow pattern map for micro-fin tube with 0° helix angle is generally similar to that for the smooth tube. For the tube with 10° and 18° helix angle, the annular flow occurs at lower vapor quality and lower mass flux. The proposed map shows good agreements when compared with the visualization and reflects the downward shift (to lower mass flux and vapor quality conditions) of the SW-WA transition with the increase of the helix angle. In order to further validate the proposed model, the flow pattern transitions calculated from the equations are also compared with the experimental data of the micro-fin tube in literature. The results show that the modified map increase the prediction accuracy of the flow patterns in the micro-fin tube.